INFOKUS: UPAYA PENINGKATAN AKTIVITAS MAHASISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DI PERGURUAN TINGGI - JULIARDI S.H, BUDI (STKIP PGRI Sumatera Barat, 2010)
The use of media in the learning process should be base on an objectivecriterion which includes the learning goal (basic and standard competence), thelearning activities and evaluation. This research is class experience in solving thedecreasing motivation and enthusiasm. As a medium in teaching civics, infocusshould be selected on the basis of its contens. The research was divided into twocycles, of which the result was analysed qualitatively with categorical andfunctional parameter through interactive model. The first cycle gave the expectedresults but needed to maximized. After infocus was used, 71 % of the studentsshowed an improved motivation. This could be seen from their participation in theclass discussion. In the second cycle, the learning process showed its maximumresult, in which 94 % of the students gave their full participation in the lesson.